Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physreva.96.053602
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Floquet state population and observing micromotion in a periodically driven two-body quantum system

Abstract: Near-resonant periodic driving of quantum systems promises the implementation of a large variety of novel quantum states, though their preparation and measurement remains challenging. We address these aspects in a model system consisting of interacting fermions in a periodically driven array of double wells created by an optical lattice. The singlet and triplet fractions and the double occupancy of the Floquet states are measured, and their behavior as a function of the interaction strength is analyzed in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 64 publications
1
71
0
Order By: Relevance
“…In ultrafast spin dynamics experiments, very intense laser pulses are used, and thus, it might be relevant to consider how heating might affect the validity of our approach. Recent theoretical [62][63][64] and experimental [65] works have shown that the energy absorption rate is exponentially suppressed for high-frequency laser pulses, i.e., for ω/W 1, where W ∝ t 1 is the fermionic bandwidth, and this condition holds in ultrafast experiments with optical laser pulses. Thus, rapidly driven systems have a very long prethermalization period, implying that the evolution of these systems in the presence of short laser pulses can be safely described by our formalism.…”
mentioning
confidence: 94%
“…In ultrafast spin dynamics experiments, very intense laser pulses are used, and thus, it might be relevant to consider how heating might affect the validity of our approach. Recent theoretical [62][63][64] and experimental [65] works have shown that the energy absorption rate is exponentially suppressed for high-frequency laser pulses, i.e., for ω/W 1, where W ∝ t 1 is the fermionic bandwidth, and this condition holds in ultrafast experiments with optical laser pulses. Thus, rapidly driven systems have a very long prethermalization period, implying that the evolution of these systems in the presence of short laser pulses can be safely described by our formalism.…”
mentioning
confidence: 94%
“…The atoms interact via a repulsive on-site interaction energy U , which can be tuned in a range between 5 and 10 kHz using a magnetic Feshbach resonance. The drive consists of a sinusoidal modulation of the lattice position in time, which in a comoving frame correponds to a modulation of the energy offset ∆ tot (τ ) = ∆ 0 + ∆(τ ) within the dimers [27]. We simultaneously apply two frequencies ω/(2π) and 2ω/(2π) to break TRS.…”
mentioning
confidence: 99%
“…In 5. We note that while agreement is good in the first half of the cycle, it becomes less reliable in the second half.…”
Section: Driven Landau-zener Modelmentioning
confidence: 75%
“…In quantum systems, a well-known consequence of periodic driving is the Rabi oscillation in a twolevel system [2]. More recently, the repertoire of such phenomena has been expanded to many-body quantum systems [3][4][5], including the appearance of non-equilibrium topological phases [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and, in the presence of interactions and/or disorder, many-body localized phases [20][21][22] that exhibit subharmonic oscillations, thus realizing a time crystal [23][24][25][26]. Also, recent experimental advances have allowed the realization of driven optical lattices [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%